COMPOSITIONAL TECHNIQUES AND ORNAMENTATION OF MEDIEVAL AZERBAIJAN AND DAGESTAN CARPETS IN THE DECORATION OF DAGESTAN MONUMENTS OF STONE-CUTTING ART OF THE 14TH-15TH CC - Mammaev, M M (History, Archeology and Ethnography of the Caucasus, 2016)
Basing on the comparative study of the ornament of Azerbaijan and Dagestan carpets and that of Dagestan monuments of stone-cutting art of the 14th-15th centuries, the author of the article shows the influence of some compositional techniques and carpet ornamentation on the decoration of Medieval Muslim carved gravestones from the villages of Kubachi and Kumukh, which are vertically set stone blocks of quadrangular or trapezoidal shape. The author notes that in the decoration of the headstones there are some elements, used in the decoration of prayer rugs, which has a form of highly stylized picture of mihrab. Thus, the decoration shares similarities with the carpet ornamentation in terms of the organic interconnection of all elements of the compositions, their proportionality and balance.